Os atrasos no reconhecimento de perdas esperadas podem agravar a retração dos empréstimos bancários em períodos de crise financeira no Brasil? - Formentini, Bruno Fraislebem (2016)
This study aims to analyze the association between bank loans, the requirement of regulatory capital, the provision methodology in periods of recession and the expansion of the Brazilian banking industry. The survey analyzed the flow of past, present and future provisions, in order to identify the relationship between banks and minor delays in the recognition of expected losses, according to the provision rules set out in Resolution 2,682/99, the National Monetary Council (CMN), adopted by banks operating in Brazil. A mixed accounting model, which broadly has incurred and expected loss characteristics. The purpose was to determine whether the banks that delay the recognition of credit losses are less likely to borrow in times of financial crisis, as a result of regulatory capital constraint. The sample consisted of 64 banks operating in Brazil in commercial and multiple segments, listed and authorized by the Brazilian Federal Reserve (BCB) and Caixa Economica Federal (CEF), during the years 2008-2013, totaling 1,472 observations per variable. The database used in this study was obtained through information collected in Quarterly Financial Information reports, balance sheets and 50 greater banks available in the information for economic and financial analysis on the site of the Brazilian Federal Reserve (BCB). The results of this research demonstrate that association between regulatory capital and bank loans will be higher during periods of recession and the pro-cyclicality of bank loans occur to a lesser extent in banks with lower delays in the recognition of the expected loss. The survey also studied the credit behavior and the main contribution of this research to literature is the finding that banks with minor delays in the recognition of losses can mitigate the recession by reducing the pro-cyclicality of credit expansion, which minimizes one of the main depth factors of the financial crisis, due to the credit crunch with future concerns and uncertainties with the inadequacy of capital.